The State of Problem Solving Skills in General Secondary Biology Laboratory Activities - Eshete, Akalewold (The Ethiopian Journal of Education, 2021)
: Though current education & training policy advocates problem solving approach in secondary school curriculum, no subsequent document is available to translate experiences into a material that develops such skills. Hence, curriculum developers and commissioned writers employed differently their own intuitions of the concept. This paper inquires into the state of problem solving skills in general secondary biology curriculum materials. All the laboratory activities suggested were taken as the source of information. A conceptual framework and different content analysis schemes were employed to determine the types of problem, degree of openness and their demands for problem solving skills. It was found that all the activities suggested (N=79) were well structured and well- defined problems. In almost all the cases, students were required to suggest only brief responses and the most important problem solving skills were not represented at all. As a conclusion, it can be argued that it is difficult to expect high school students to transfer such skills into their real life situation that requires biological literacy. This paper recommends the need to re-conceptualize the concept, revise and refine general secondary biology curriculum through developing a workable problem-solving framework.